Disruption of diphenylalanine assembly by a Boc-modified variant - Creasey, Rhiannon; Louzao, Iria; Arnon, Zohar; Marco, Pini; Adler-Abramovich, Lihi; Roberts, Clive J.; Gazit, Ehud; Tendler, Saul J.B. (Royal Society of Chemistry, 2016)
Peptide-based biomaterials are key to the future of diagnostics and therapy, promoting applications such as tissue scaffolds and drug delivery vehicles. To realise the full potential of the peptide systems, control and optimisation of material properties are essential. Here we invesigated the co-assembly of the minimal amyloid motif peptide, diphenylalanine (FF), and its tert-butoxycarbonyl (Boc)-modified derivative. Using Atomic Force Microscopy, we demonstrated that the co-assembled fibers are less rigid and show a curvier morphology. We propose that the Boc-modification of FF disrupts the hydrogen bond packing of adjacent N-termini, as supported by Fourier transform infrared and fluorescence spectroscopic data. Such rationally modified co-assemblies offer chemical functionality for after-assembly modification and controllable surface properties for tissue engineering scaffolds, along with tunable morphological vs. mechanical properties.